Building Entrepreneurial Spirit in Students Through Islamic Economic Literacy - Heidy Akhadi; Ahmad Maulidizen; Abdul Haris Muchtar (SocietalServe: Journal of Community Engagement and Services, 2025)
This community service program titled "Building Entrepreneurial Spirit in Students Through Islamic Economic Literacy" was held on May 24, 2025, in Semarang under the Sharia Young Leader BSI Maslahat initiative. It aimed to empower underprivileged university students by integrating Islamic economic knowledge with personal motivation and spiritual development. The program applied a fun-learning approach to deliver modules on barakah (blessing), Islamic work ethics, fiqh muamalah, and Sharia-compliant contracts (akad), as well as motivational training based on the ESQ Matrix. A total of 51 participants underwent both pre- and post-tests, showing a significant knowledge increase from an average score of 62.39 to 84.58. Feedback indicated high satisfaction, with average scores above 5.7 out of 6 for both content and trainer performance. Participants appreciated the relevance and applicability of the material and suggested enhancements such as more interactive sessions and follow-up resources. The program successfully contributed to students’ understanding of ethical entrepreneurship and Islamic economic principles, supporting their role as future contributors to the Sharia economic ecosystem in Indonesia.